Equitable Law Enforcement Against Law Enforcement Officers in Criminal Acts of Corruption - Andi Apriyanto; Siswantari Pratiwi; Parbuntian Sinaga (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
The pattern of eradicating corruption by punishing perpetrators with severe criminal sanctions and even up to the death penalty must be upheld to prevent acts of corruption. However, in practice, the criminal sanctions given by court judges to perpetrators are still light, even when the perpetrators are law enforcement officials such as the Prosecutor General's Office. The problem is how to consider the judges of the DKI Jakarta High Court Number 10/Pid.Sus-TPK/2021/PT.Dki and the Decision of the Central Jakarta District Court Number 11/Pid.B/TPK/2008/PN.Jkt.Pst in imposing criminal sanctions by Prosecutor Pinangki and Prosecutor Urip Tri Gunawan? The research method used is normative juridical research using secondary data. The results of the study stated that the consideration of the DKI Jakarta High Court Judge Number 10/Pid.Sus-TPK/2021/PT.Dki and the Decision of the Central Jakarta District Court Number 11/Pid.B/TPK/2008/PN.Jkt.Pst in imposing criminal sanctions that were carried out by Prosecutor Pinangki and Prosecutor Urip Tri Gunawan was based on mitigating and aggravating matters which led to disparities. This is caused by structural factors, substance factors, and cultural factors.